2014
DOI: 10.1371/journal.pone.0115818
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into Secreted Ribonuclease Structure: Binase Is a Natural Dimer

Abstract: The biological effects of ribonucleases (RNases), such as the control of the blood vessels growth, the toxicity towards tumour cells and antiviral activity, require a detailed explanation. One of the most intriguing properties of RNases which can contribute to their biological effects is the ability to form dimers, which facilitates efficient RNA hydrolysis and the evasion of ribonuclease inhibitor. Dimeric forms of microbial RNase binase secreted by Bacillus pumilus (former B. intermedius) have only been foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…The immunoblot analysis showed that anti-binase antibodies interact with low order oligomers of balifase too ( Figure 4(d) ). Therefore, we can conclude that balifase can exist in oligomeric forms in solution but unlike binase, not under natural conditions of biosynthesis [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunoblot analysis showed that anti-binase antibodies interact with low order oligomers of balifase too ( Figure 4(d) ). Therefore, we can conclude that balifase can exist in oligomeric forms in solution but unlike binase, not under natural conditions of biosynthesis [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…To estimate in-gel RNase activity of proteins we performed zymography analysis as described in [ 25 ]. Proteins were separated in 15% polyacrylamide gel with 0.1% SDS (SDS-PAGE) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is known that peak asymmetry could indicate the presence of different oligomeric forms of enzyme in the sample [33]. Moreover, it was found that binase forms very stable dimers which do not dissociate during SDS/PAGE [25]. These facts denoted the possibility of balnase to dimerize.…”
Section: Discussionmentioning
confidence: 99%
“… Ribonuclease binase from B.pumilus was cleaved by trypsin and the cleavage fragments were analysed on HPLC LC-MS/MS system (Bruker, Germany) 60 . The numbers denote determined oligopeptide masses.…”
Section: Figurementioning
confidence: 99%